The analysis of Last Interglacial (MIS 5e) relative sea-level indicators: Reconstructing sea-level in a warmer world - Rovere A.; Raymo M. E.; Vacchi M.; Lorscheid T.; Stocchi P.; Gomez-Pujol L.; Harris D. L.; Casella E.; O'Leary M. J.; Hearty P. J. (Earth-Science Reviews, 2016)
The Last Interglacial (MIS 5e, 128–116ka) is among the most studied past periods in Earth's history. The climate at that time was warmer than today, primarily due to different orbital conditions, with smaller ice sheets and higher sea-level. Field evidence for MIS 5e sea-level was reported from thousands of sites, but often paleo shorelines were measured with low-accuracy techniques and, in some cases, there are contrasting interpretations about paleo sea-level reconstructions. For this reason, large uncertainties still surround both the maximum sea-level attained as well as the pattern of sea-level change throughout MIS 5e. Such uncertainties are exacerbated by the lack of a uniform approach to measuring and interpreting the geological evidence of paleo sea-levels. In this review, we discuss the characteristics of MIS 5e field observations, and we set the basis for a standardized approach to MIS 5e paleo sea-level reconstructions, that is already successfully applied in Holocene sea-level research. Application of the standard definitions and methodologies described in this paper will enhance our ability to compare data from different research groups and different areas, in order to gain deeper insights into MIS 5e sea-level changes. Improving estimates of Last Interglacial sea-level is, in turn, a key to understanding the behavior of ice sheets in a warmer world.